Pengaruh NPF, FDR, dan BOPO terhadap Profitabilitas (ROA) pada BPRS di Indonesia Tahun 2021-2024 - Al Hadziq Ibnu Yunus; Hesi Eka Putri; Bustamar; Yuwarman Mansur (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
This research is motivated by the phenomenon of Non-Performing Financing, Financing to Deposit Ratio, and Operating Costs and Operating Income, which have become a concern along with the development of BPRS. These aspects are also useful for measuring the level of business efficiency and profitability achieved by BPRS. A healthy bank is one whose profitability, as measured by profitability, continues to increase above the established standards.This research uses a quantitative approach. The population in this study was all BPRS registered in Indonesia during the 2021-2024 period. Thus, a sample of 174 BPRS was obtained. The data used were secondary data sourced from published BPRS annual financial reports. Data analysis was conducted using multiple linear regression analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), partial (t-test) and simultaneous (F-test) hypothesis tests, and the coefficient of determination.The results of this study indicate. The effect of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Costs and Operating Income (BOPO) on Return on Assets (ROA) from the results of the study can be known Ho4 = There is no significant effect of NPF, FDR and BOPO variables simultaneously on ROA on BPRS in Indonesia. Ha4 = There is a significant effect of NPF, FDR and BOPO variables on Profitability (ROA) on BPRS in Indonesia. In this test, it is done by setting a significance level of 0.05 or 5%. Based on the statistical table above, the calculated F is 2,875. While the F table is determined using a 95% confidence level, α = 5% or 0.05, df1 = k (Number of independent variables) and df2 = n – k – 1 (n = number of samples, k = number of independent variables). Thus, df1 = 3 and df2 = 174 – 3 – 1 = 170, then the F table value is 2.66. It can be concluded that the calculated F > F table (2.875 > 2.66) with a significance level of 0.000 < 0.05, meaning that Ho4 is rejected and Ha4 is accepted. Thus, it can be explained that the NPF, FDR and BOPO variables have a positive and significant effect simultaneously on Profitability (ROA) in BPRS in Indonesia.